Effect of Job Demand, Compensation, and Personality Traits on Organizational Commitment Moderated by Work by Remote Employees in the Fast Moving Consumer Goods (FMCG) Sector - Johannes JOHANNES; Nandan LIMAKRISNA; Sarfilianty ANGGIANI (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to analyze the effect of job demand, compensation, and personality traits on organizational commitment which is moderated by work by remote employees in the fast-moving consumer goods (FMCG) sector. This research method uses a quantitative approach, tested with Structural. Equation Modeling-Partial Least Squares (SEM-PLS). The sample method uses judgment sampling, by taking data from 555 permanent employees who have worked for at least 1 year in fast moving consumer goods (FMCG) industrial companies. The results of the study show that there is a negative effect of job demand on organizational commitment. there is a positive effect of compensation and personality traits on organizational commitment. there is an effect of job demand on organizational commitment moderated by work by remote employee, and there is no effect of compensation and personality traits on organizational commitment which is moderated by work by remote employee